2001
DOI: 10.1046/j.1471-4159.2001.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulation of cyclooxygenase‐1 in neuroblastoma cell lines by retinoic acid and corticosteroids

Abstract: Cyclooxygenases-1 and -2 are both expressed in neuronal cells in vivo. In the neuroblastoma cell lines NG108 and N2a, however, only cyclooxygenase-1 was detectable. Differentiation of the cells with retinoic acid increased cyclooxygenase-1 mRNA and protein expression within 24 and 48 h, respectively. A further increase was observed when the cells were concomitantly treated with the glucocorticoid dexamethasone (a 2±3-fold increase compared with retinoic acid alone). In the absence of retinoic acid, dexamethaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 48 publications
3
20
0
Order By: Relevance
“…Dexamethasone causes a dose-and time-dependent increase in expression and activity of prostaglandin D2 synthase in neuronal cultures (Garcia-Fernandez et al 2000) and dexamethasone or corticosterone treatment increases the pro-inflammatory leukotriene synthesis enzyme 5-lipoxygenase in both the hippocampus (Uz et al 1999) and macrophages (Riddick et al 1997). Finally, dexamethasone alone or more robustly in conjunction with retinoic acid, causes increased COX-1 expression in neuroblastoma cell lines (Schneider et al 2001).…”
Section: 3mentioning
confidence: 99%
“…Dexamethasone causes a dose-and time-dependent increase in expression and activity of prostaglandin D2 synthase in neuronal cultures (Garcia-Fernandez et al 2000) and dexamethasone or corticosterone treatment increases the pro-inflammatory leukotriene synthesis enzyme 5-lipoxygenase in both the hippocampus (Uz et al 1999) and macrophages (Riddick et al 1997). Finally, dexamethasone alone or more robustly in conjunction with retinoic acid, causes increased COX-1 expression in neuroblastoma cell lines (Schneider et al 2001).…”
Section: 3mentioning
confidence: 99%
“…Design and statistical analyses Studies were designed as reported by others using cell line models (Chiaramonte et al, 1998;Schneider et al, 2001). Thus, each experiment was replicated using triplicate (or a greater number of replicate) assays from duplicate cultures for each test condition.…”
Section: Secondary Antibody Was Alexa Fluor 680 Goat Anti-rabbit Igg mentioning
confidence: 99%
“…Total protein was determined using the BCA assay (Pierce Chemical Co., Rockford, IL, USA) and 20 mg protein was loaded per lane on SDS PAGE. Resolved proteins were transferred to nitrocellulose and detected in Western blot using (1/1000) polyclonal rabbit anti-PPAR-g antibody or rabbit anti-GLUT-4 antibody, and secondary antibody (1/5000) Alexa Fluor 680 goat anti-rabbit IgG and scanned on an infra-red fluorescence imager (Odyssey; LI-COR, Inc., Lincoln, NE, USA).Design and statistical analyses Studies were designed as reported by others using cell line models (Chiaramonte et al, 1998;Schneider et al, 2001). Thus, each experiment was replicated using triplicate (or a greater number of replicate) assays from duplicate cultures for each test condition.…”
mentioning
confidence: 99%
“…However, retinoid isomers including ATRA and 9-cis-RA were described to induce COX-1 in human premonocytic U937 cells 20 and human Arsenic inhibits ATRA-induced COX-1 in NB4 cells A Habib et al neuroblastoma cell lines. 21 ATRA-induced COX-1 upregulation may be mediated by the Sp1 transcription factor, which is significantly upregulated during myeloid differentiation, and has been reported to mediate ATRA responsiveness of several genes devoid of RAR-responsive element (RARE) motifs. [27][28][29] In that sense, the COX-1 promoter contains two Sp1-binding sequences but no canonical RARE.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Retinoid isomers including ATRA and 9-cis-RA were described to induce COX-1 in human premonocytic U937 cells. 20 Retinoic acid was also described to induce COX-1 in human neuroblastoma cell lines 21 and COX-2 in synergy with platelet activating factor. 22 We have recently demonstrated that ATRA induces COX-1 but not COX-2 in NB4 cells and in blasts from patients with APL.…”
Section: Introductionmentioning
confidence: 99%